2021
DOI: 10.1002/jbm4.10567
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Bolus Is Bogus—A Narrative Review

Abstract: In this review we summarize the impact of bolus versus daily dosing of vitamin D on 25(OH)D and 1,25(OH) 2 D levels, as well as on key countervailing factors that block vitamin D functions at the cellular level. Further, we discuss the role of bolus versus daily dosing of vitamin D for several health outcomes, including respiratory infections and coronavirus disease 2019 (COVID-19), rickets, falls and fractures, any cancer, and cancer-related mortality. This discussion appears timely because bolus doses contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 103 publications
(144 reference statements)
1
35
0
4
Order By: Relevance
“…Given the recent results of the randomized placebo-controlled trial of a one-time bolus of high-dose Vit D, which showed no improvement in hospital length of stay in COVID-19 patients [ 36 ], it is noteworthy that Vit D use by patients in our study was generally low-dose daily administration from days to weeks post-COVID-19 diagnosis. There is ample evidence that chronic, daily Vit D dosing is superior to bolus high-dose administration for many reasons, several of which have been summarized in recent publications [ 122 , 123 , 124 ]. For example, a single high dose of Vit D, versus daily administration, has been reported to activate the 24-hydroxylase enzyme (CYP24A1), leading to increased production of the inactive form of Vit D (i.e., 24,25(OH) 2 D 3 ) [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent results of the randomized placebo-controlled trial of a one-time bolus of high-dose Vit D, which showed no improvement in hospital length of stay in COVID-19 patients [ 36 ], it is noteworthy that Vit D use by patients in our study was generally low-dose daily administration from days to weeks post-COVID-19 diagnosis. There is ample evidence that chronic, daily Vit D dosing is superior to bolus high-dose administration for many reasons, several of which have been summarized in recent publications [ 122 , 123 , 124 ]. For example, a single high dose of Vit D, versus daily administration, has been reported to activate the 24-hydroxylase enzyme (CYP24A1), leading to increased production of the inactive form of Vit D (i.e., 24,25(OH) 2 D 3 ) [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Daily, weekly, or monthly vitamin D supplementation, at equivalent doses, lead to similar increases in 25(OH)D serum concentrations, when measured after 2 to 3 months [ 65 , 66 , 67 ]. Adherence may be better with intermittent vitamin D dosing, but there are also concerns that high intermittent vitamin D doses may be less beneficial or might even be harmful in certain settings [ 67 , 68 , 69 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Daily, weekly, or monthly vitamin D supplementation, at equivalent doses, lead to similar increases in 25(OH)D serum concentrations, when measured after 2 to 3 months [ 65 , 66 , 67 ]. Adherence may be better with intermittent vitamin D dosing, but there are also concerns that high intermittent vitamin D doses may be less beneficial or might even be harmful in certain settings [ 67 , 68 , 69 ]. In view of the available evidence from clinical vitamin D trials and some pathophysiological considerations (e.g., altered vitamin D metabolism with high intermittent vitamin D doses), a daily vitamin D dosing schedule should rather be preferred, but when exceedingly high intermittent vitamin D doses are avoided, a weekly or monthly dosing schedule can also be applied [ 66 , 67 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large meta-analysis reported no beneficial effect of vitamin D versus placebo or vitamin D + calcium versus calcium [ 64 ]. However, this meta-analysis included studies that recruited a relatively low number of participants or used either very low daily doses (400 UI/day) or very high intermittent (300,000–500,000 IU/year) doses, two actions known to have either no effect (very low doses) or even detrimental effects (very high intermittent doses) on the risk of falls and fractures by mechanisms not yet understood [ 65 ]. When the analysis was restricted to RCTs that used daily vitamin D doses of 800–1000 IU (8 RCTs), the conclusion was that vitamin D reduced the risk of fracture by 14% (RR 0.86, 95% CI 0.75–0.98) compared to placebo [ 66 ].…”
Section: Vitamin D Supplementation and Fractures In Ckdmentioning
confidence: 99%